Behind the scenes of the healthcare COVID-19 pandemic crisis: potential affecting factors of healthcare work sustainability in Romania during 2020–2022 - Savu, Cristina; Armaș, Iuliana; Burcea, Marin; Dobre, Daniela (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic represented a great disturbance for medical systems around the world, putting medical personnel on the front lines of the fight against the SARS-Cov2 virus. This fight was particularly impactful in countries with medical systems already facing various challenges, including Romania; where the pandemic unfolded in five waves that severely affected the psychological and physical well-being of medical professionals in terms of overload and continuous exposure to health threats. Against this background, our research aims to investigate the mediating role of the perception of healthcare workers of their own state of health in relation to pandemic stress, work-family conflict, work engagement, meaning of and commitment to work, satisfaction of basic psychological needs, patient care and burnout symptoms, and the dynamics of this relations during all five pandemic waves in Romania, which span from March 2020 to April 2022. This cross-sectional study is based on an online snowball sampling of 738 health workers from 27 hospitals. Panel research is limited to a maximum of 61 respondents for two successive waves. The results indicate statistically significant correlations between the perception of health risks and all the other selected factors excluding patient care, which seems to be above the own health perception. Health workers with higher levels of positive perceived health are better at managing pandemic stress, burnout effects and work-family imbalances. Adaptive behaviours and attitudes towards COVID-19 pandemic threats could be identified in later pandemic waves due to the progress in terms of medical protocols and procedures.